Optimal control of heat pump water heater-instantaneous shower using integrated renewable-grid energy systems. (1st September 2017) - Wanjiru, Evan M.; Sichilalu, Sam M.; Xia, Xiaohua
Abstract: Developing countries are grappling with energy and water insecurity, impelling governments to encourage end-users to conserve and efficiently consume these vital resources. With water heating being among the largest energy users in residential buildings, it is imperative that the efficiency and conservation of both energy and water are achieved. Heat pump water heaters (HPWHs) are a superior choice in efficiently providing domestic hot water. However, there are still challenges in their optimal operation and high initial cost in developing nations. Further, since they are normally centrally located in a house, there are water and associated energy losses during hot water conveyance to the end-use, as the cold water has to be poured away. This paper introduces an optimal control strategy of a hybrid HPWH and instantaneous shower powered using integrated renewable energy systems. This strategy has the potential to save 23.4% and 19 l of energy and water in a day respectively, while also promising lower energy and water bills to the end users. Further economic benefit can be achieved through the sale of excess renewable energy back to the grid through an appropriate feed-in tariff.